2013
DOI: 10.1111/jse.12054
|View full text |Cite
|
Sign up to set email alerts
|

Systematic significance of seed morphology in the genus Veronica (Plantaginaceae), with special reference to the Egyptian taxa

Abstract: Seed morphology of 29 taxa including 9 subgenera belonging to the genus Veronica was compared using scanning electron microscopy to assess their diagnostic value for systematic studies. Subgenus Beccabunga is the largest in this study represented by nine taxa. Seed surface often varies from ridged reticulate or verrucose/granulate reticulate to rugose-reticulate. Seed color and size have limited taxonomic significance as their variation is uninformative. Thereagainst, seed shape and seed coat ornamentation pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…lilacina, and V. persica) form an isolated group. Based on the infrageneric classification as done in [47] [32,34]), that seed morphological data can be employed to evaluate the relationships of taxa within the genus and that seed characters can also provide additional support to infrageneric discrimination in Veronica.…”
Section: Systematic Implications Of Seed Charactersmentioning
confidence: 99%
See 2 more Smart Citations
“…lilacina, and V. persica) form an isolated group. Based on the infrageneric classification as done in [47] [32,34]), that seed morphological data can be employed to evaluate the relationships of taxa within the genus and that seed characters can also provide additional support to infrageneric discrimination in Veronica.…”
Section: Systematic Implications Of Seed Charactersmentioning
confidence: 99%
“…In the past, the variation in seed morphology has been used variously in plant systematics ranging from identification [16,17] and taxonomic circumscription [18,19] to phylogenetic inference [20,21] and character-state evolution [22,23]. Both macro-and micromorphological seed characters have been shown to be of essential systematic importance within and among the genera of traditional Scrophulariaceae, Orobanchaceae, and Plantaginaceae [24][25][26][27][28][29][30][31][32][33][34][35], in which seed morphological characters have been used widely to differentiate the different taxa or to find affinities between them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of many plant groups have shown that seed morphology and anatomic features are rather conservative, and hence taxonomically important (Barthlott 1981;1984;Werker 1997;Abdel Khalik 2010;Abdel Khalik & Hassan 2012;Hassan & Abdel Khalik 2014).…”
Section: Introductionmentioning
confidence: 99%
“…V. intercedens is similar to V. capillipes with a cyathiform seed shape, unlike V. viscosa where it is flattened. The seed shape and seed coat of V. rubrifolia are reported to be cyathiform and cristate at dorsal face (Munoz-Centeno et al, 2006;Hassan and Khalik, 2014). In this study, seed shape of V. rubrifolia subsp.…”
Section: Resultsmentioning
confidence: 63%